Legal Loopholes in the Application for Termination of Investigation by Investigators Due to the Absence of Clear Standards in Determining Sufficient Evidence - John Piter Tampubolon; Rineke Sara (Greenation Research & Yayasan Global Resarch National, 2025)
This study examines the legal gaps that arise in investigators' requests to terminate investigations based on Article 109 paragraph (2) of the Criminal Procedure Code, which authorizes the filing of an SP3 (Sufficient Evidence Order) due to